STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PENGOLAHAN LIMBAH SABUT KELAPA MENJADI MEDIA TANAM COCOPEAT BERBASIS EKONOMI HIJAU DI DESA MEDANA, KECAMATAN TANJUNG, KABUPATEN LOMBOK UTARA - Azhim, Ahmad Fauzil; Mahram, B.Hindri; Rahmani, Hamida; Sukardi, Huda Wahyuda; Putri, Indah Yuniarti; Azwalina, Mira; Nazir, M. Kaspun; Adjani, Naylah Hanifah; Faradila, Rahma Berliani; Taibah, Zuriatun (Universitas Mataram, 2025)
The utilization of coconut husks in Medana Village, Tanjung District, North Lombok Regency has not been optimal because most of them are simply discarded or burned. This condition has prompted the need for a community empowerment strategy so that this waste can be processed into products with economic value. This community service program aims to provide training on processing coconut husks into cocopeat as a sustainable planting medium that supports the concept of a green economy. The method used is Participatory Extension, which actively involves the community in every stage, from processing the material and packaging to digital marketing socialization to expand market reach. The results of the activity show an increase in the community's knowledge and skills in processing coconut husks, while also opening up new business opportunities that can increase income and preserve the environment.